Analysis of Mangrove Community in The Bagek Kembar Essential Ecosystem Area, West Lombok - Harsa Naunik Qudraty; Lalu Japa; Eni Suyantri (Jurnal Biologi Tropis, 2023)
: Bagek Kembar Essential Ecosystem is one of mangrove ecosystem in the Sekotong Bay. In some part of the area has also been used as a pond for mariculture activity so, it can influence the composition and diversity of mangroves in that area. This research was conducted to determine the species composition, importance value index, and diversity of mangrove species. Data of mangrove vegetation were collected in a method combination of line transects and quadrats. Total of 11 transects and 33 quadrats were layed out in the area of the Bagek Kembar mangrove ecosystem. The results of this research showed that there were seven mangrove species as member of 4 genera and 4 families. The highest species dominant index and density was Avicennia marina. The mangrove species diversity index for tree and sapling was 1,000 and 1,003, respectively (both in medium categories) and the diversity index for seedling was in low category (0,676).